Managing in Latin America: Common issues and a research agenda - Vassolo, Roberto Santiago (2011)
Latin America is a paradoxical region. It has unique conditions that make it one of the most attractive contexts worldwide for doing business, but it also faces serious challenges that severely underscore these opportunities. We apply a simple framework of analysis to describe the Latin American business environment and detect research opportunities. For that, we focus on four aspects of the region: (1) the institutional context, (2) the macroeconomic environment, (3) the consumer profile, and (4) the natural resource endowments. We summarize firms' strategic choices that result from this context and analyze their consequences for new business creation, incumbents' survival and growth, and sources of competitive advantages. We conclude by outlining a management research agenda.